Study on evaluation of elastic modulus of crumb rubber concrete in meso-scale. (9th May 2022) - Cai, Xianglei; Zhang, Lihua; Pan, Weidong; Wang, Weilong; Guan, Qingfa; Zhai, Shengtian; Liu, Laibao; Zhang, Yunsheng
Highlights: An improved model based on Mori-Tanaka method is proposed to predict the elastic modulus of crumb rubber concrete. The importance of characteristic strain of ordinary aggregates and rubber crumbs is included in the model. The prediction is more realistic with the effect of pore is introduced into concrete model when the rubber crumbs is contained. The importance of the factors for the elastic modulus prediction of crumb rubber concrete can be evaluated by this model. Abstract: Crumb rubber concrete (CRC) has attracted significant attention as a typical reclamation and recycling of solid wastes, and endows concrete with excellent impact resistance. However, the elastic modulus of CRC can be affected by the uncertain properties of rubber crumbs. In this study, an improved Mori-Tanaka model (IMT) was proposed to estimate the elastic modulus of CRC in meso-scale. The model establishes the quantitative relationship between the elastic modulus and volume fraction of all constituent materials (ordinary aggregate, rubber crumbs, and cementitious materials) involved in CRC and its interface transition zone (ITZ). The results indicate that the error of IMT predicted elastic modulus of CRC is about 3.9%, which is reduced by about 8.9% compared with the Mori-Tanaka model (MT model). Further, the importance of different factors influencing the elastic modulus of CRC is assessed by the IMT model. The specific attributes of rubber crumbs (particle size and volume fraction), ITZ, and cementitious materials (the elastic modulus) have been shown to affect the elastic modulus of CRC significantly. Thus, the IMT model can be beneficial for the design of CRC with specific elastic modulus by considering the effect of different constituents.